Don’t be abstract: Crafting an impactful abstract for educational technology research - Corrin, Linda; Huijser, Henk; Han, Feifei; Lodge, Jason (Australasian Journal of Educational Technology, 2024)
The abstract is a key element of a research article that can enhance the utility, discoverability and impact of the work presented. However, the quality and consistency of abstracts can vary, and the state of abstracts in the educational technology field has received little attention to date. In this editorial, we examine the purpose, structure and future of the abstract in educational technology research to provide advice on how to write a good and impactful abstract. A list of 14 elements derived from the literature was used to analyse the abstracts of the first 10 articles published in 2024 from each of the top 10 educational technology journals ranked by Google Scholar (n = 100). Elements such as background, aim, methods, results and implications were found to be present in most abstracts, although there is room for improvement in clarity in some cases. Other elements, including research questions, hypotheses and future directions, are not often incorporated, indicating these elements may not be necessary in this context. These findings can be used by authors to structure an impactful abstract and also highlight elements (e.g., theoretical framework, sample size and context) that should be included to improve discoverability of published work.